Proposed Indoor Test Procedure to Quantify Pesticide Treatment Effects on Seed Consumption by Birds. (27th December 2019) - Esther, Alexandra; von Blanckenhagen, Felix; der Heiden, Angela an; Dürger, Joanna; Kozyczkowska‐Kneffel, Dominika; Ludwigs, Jan‐Dieter; Sadowski, Jan; Shadid, Maisam; Gabriel, Doreen
Abstract: Pesticides used in seed coatings can influence seed consumption by birds and, therefore, actual exposure risk for them. A quantification of such effects on consumption is currently not regarded as a refinement factor in environmental risk assessments, although it is a possible option and should be considered, for example, for comparing exposure risk of different pesticides. It can highlight avoidance behavior, preventing birds from taking up lethal or sublethal pesticide doses. To formulate a standard, we developed an indoor test procedure based on established pen test methods, including 2‐ and no‐choice phases with hunger periods. During testing, the highest standards of animal welfare were applied. Statistical approaches were used to determine the most appropriate number of replicates and for analysis. The effect on consumption of seeds is expressed as the ratio of consumed treated to untreated seeds. This consumption factor can be applied in avian risk assessments for seed treatments equivalent to an avoidance factor. We present, as an example, an application of the procedure to obtain a seed‐ and species‐specific consumption factor for oilseed rape seeds ( Brassica napus ) provided untreated and treated with fungicides to greenfinches ( Carduelis chloris ) and Japanese quail ( Coturnix japonica ). Overall, bird constitution was not negatively affected by the test procedure in either species. The test procedure was suitable for showing differences in expected consumption patterns, such as greater avoidance of treated seeds in 2‐choice than in no‐choice tests. However, the consumption differed between species and fungicide treatments, allowing us to rank avoidance effects of different fungicides. Using the presented standard procedure to generate comparable pesticide‐ and species‐specific consumption factors for more species and seed treatments may result in refinement of default values and reduce animal trials in different designs in the future. Environ Toxicol Chem 2020;39:359–370. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.